THE COLLABORATED TRADE SHOWS AND COMMUNITY ENTREPRENEURS: HOW THEY BENEFIT SMALL MEDIUM-SIZED ENTERPRISES - Somariah Fitriani; Sintha Wahjusaputri; Ahmad Diponegoro (Jurnal Manajemen dan Kewirausahaan, 2021)
The study intended to elaborate on the contribution of exhibitions and community for the development of small and medium-sized enterprises (SMEs). This qualitative research employed a case study design, as the group of SMEs in Tangerang Selatan became the analysis unit. 25 SMEs, which are engaged in fashion, craft, and culinary participated in the study. The researchers obtained the data from observation, interviews, and document analysis. The research has revealed that participating in exhibitions brings an economic impact on their sales ranging from 20-80 percent. In terms of the involvement of the SME community, entrepreneurs obtained a lot of beneficial impacts on the improvement of their products as well. It implied the more exhibitions the more benefits SMEs obtain.